Penerapan Nilai-Nilai Islam Dalam Meningkatkan Sportivitas Pemain Di SSB Wuled - Risdiani, Risdiani; Wijaya, M. Riski Adi; Setianto, Gigih; Febrianto, Muhammad (Musamus Journal of Physical Education and Sport (MJPES), 2024)
This study aims to analyze the application of Islamic values in shaping the sportsmanship character of soccer players at SSB Wuled. Islamic values such as discipline, honesty, cooperation, patience, and respect are instilled through direct example, discussions, and consistent practice by the coaches. The study employs a qualitative naturalisctic approach, with data collected through interviews, observations, and documentation. The results indicate that the application of Islamic values at SSB Wuled has a positive impact on the development of sportsmanship among players, though some areas still require further improvement. Additionally, the strategic role of both coaches and parents is crucial in reinforcing these values, helping to form players who are not only technically skilled on the field but also possess good character in their social lives. In conclusion, the synergy between coaches and parents in applying Islamic values is a key factor in fostering sportsmanship among early-age soccer playersAbstract should describe the entire content of the article with maximum of 300 word. It is not allowed references to figures and tables. it is written in a straightforward, concise, and must include: research objective, method, conclusion